2017
DOI: 10.1186/s41182-017-0056-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of training programs to improve human resource capacity for HIV, malaria, and TB control: a systematic scoping review of methods applied and outcomes assessed

Abstract: BackgroundOwing to the global health workforce crisis, more funding has been invested in strengthening human resources for health, particularly for HIV, tuberculosis, and malaria control; however, little is known about how these investments in training are evaluated. This paper examines how frequently HIV, malaria, and TB healthcare provider training programs have been scientifically evaluated, synthesizes information on the methods and outcome indicators used, and identifies evidence gaps for future evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…This 1-year time frame was chosen for two reasons. First, in a systematic review of training evaluation studies, we found most of the training evaluation used pretraining and post-training tests to assess short-term effectiveness of training programmes, but there is very limited evidence on the long-term impact (more than 6 months) of training participants 24. Therefore, 1 year seemed to be a suitable time period for evaluating the long-term effectiveness of a training programme.…”
Section: Methodsmentioning
confidence: 99%
“…This 1-year time frame was chosen for two reasons. First, in a systematic review of training evaluation studies, we found most of the training evaluation used pretraining and post-training tests to assess short-term effectiveness of training programmes, but there is very limited evidence on the long-term impact (more than 6 months) of training participants 24. Therefore, 1 year seemed to be a suitable time period for evaluating the long-term effectiveness of a training programme.…”
Section: Methodsmentioning
confidence: 99%
“…Although most participants have > 5 years of tenure, they do not have a lot of training in field epidemiology and data management. As reported by other studies, most of the public health trainings that the frontline workers participated in were vertical and program-specific trainings for HIV, TB, and malaria [ 22 ]. FETP-frontline is horizontal training that focuses on competencies outlined by the World Health Organization and its essential public health functions [ 23 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…However, an assessment of the quality of existing training and its effect on workforce behavior change is also important; a meta-analysis of evaluations of HIV, tuberculosis, and malaria training programs revealed that such programs are rarely robustly evaluated. 22 A systematic review recently highlighted the effectiveness of combining HCW training and supervision for improving HCW performance, although the effect size was still moderate. 23 One notable finding of this survey was how strongly linked correct malaria case management was to perceived HCW norms around case management.…”
Section: Discussionmentioning
confidence: 99%